Icthyosis Uteri with in Situ Carcinoma: Report of 2 Cases - Pathan, Almas Iqbal; Kudrimoti, Jyoti Kiran; Puranik, Shaila Chandrakant (Annals of Pathology and Laboratory Medicine, 2018)
Icthyosis uteri is a rare condition in which entire surface of the endometrium is replaced by stratified squamous epithelium. Two cases of Icthyosis uteri are reported for their rarity. The first case was of a 70 year old female with a history of lower abdominal pain and white PV (per vaginal) discharge since 3 months. The second case was of a 70 year old female with history of PV (per vaginal) spotting and breathlessness since 1 year. Gross examination of uterine cavity showed rough and irregular endometrial surface in the first case while in second case endometrium was atrophic. Microscopy of endometrium in both cases revealed total replacement of endometrial glands by stratified squamous epithelium with changes of in situ carcinoma or severe dysplasia. Cervix also showed severe dysplasia or CIN (cervical intra epithelial neoplasia) III in both the cases.